Farmer participation in cultivar evaluation: The case of beans - Ugen, Michael Adrogu; Wortmann, Charles S. (1994)
Nine advanced bean lines (MCM 5001, CAL 96, RWR 136, AFR 531, AFR 509, UGP 6088, PVA 698, SUG 50 white haricot) were tested on-farm for two seasons of 1992 in Bushenyi, Iganga, Kabale, Luwero, Mbarara, Mpigi, Mubende and Nebbi districts of Uganda. The objective was to evaluate the performance and acceptability of these promising materials under farmers conditions. Yield, seed color, seed taste, cooking time, maturity, disease reaction, growth habit and many other bean characteristics were assessed by farmers. The beans were grown in sole crop or intercropped with maize, bananas or cassava. Farmers were given 0.2 kg of seed of each variety to plant and 5-6 varieties per farm. The promising varieties were higher yielding than the farmers own cultivars in most districts. Farmer assessments of the varieties indicate that MCM 5001, CAL96, RWR 136, AFR 509 and PVA 698 are acceptable to farmers in most districts